Christian-Muslim women in religious peacebuilding, breaking cycles of violence - Furlan-Štante, Nadja (Poligrafi, 2020)
In a broader context, the main focus of this paper is the question of wom-en%s religious peacebuilding, which is understood in its widest sense, in terms of women%s active participation in building liberating theologies and societies. It is about the promotion of the full humanity of women. While elaborating this theme, the paper takes up Susan Brooks Thistlethwaite%s assertion that the %violence against women is the largest and longest global war.% Just peacemak-ing is very much an interfaith and interreligious work and should be placed as a crucial starting point of the urge for transformation of %violent% theologies and living everyday praxis. While women have been marginalised from peacebuild-ing generally, the emerging field of religious peacebuilding has been particularly challenging for women. The liberating theme of this paper is illumination of the ambivalence of invisibility and marginality of women in religious peacebuilding, good practices and future issues.
Keywords: dobre prakse; good practices; interreligious dialogue; medreligijski dialog; obstacles; ovire; religija; religijska izgradnja miru; religion; religious peace-building; women; ženske